Thermogenic hydrocarbons from the offshore Calypso hydrothermal field, Bay of Plenty, New Zealand - Botz , R.; Wehner , H.; Schmitt, M.; Worthington , T.; Schmidt, Mark; Stoffers , P. (Chemical Geology, 2002)
Hydrothermal gases from shallow seafloor vents in the Bay of Plenty, New Zealand contain CO2, CH4, and the higher gaseous hydrocarbons up to i-, n-C4H10. The gases are similar to those discharged at fumaroles on the nearby White Island. Carbon isotope compositions for CO2 fall between −3.4‰ and −5.5‰ PDB and reflect a shallow magmatic carbon source. The δ13C values of CH4 range from −24.6‰ to −28.9‰ PDB and the δD values vary between −122‰ and −135‰ SMOW. The CH4 isotope values and the presence of the higher hydrocarbon compounds such as C2H6 and C3H8 with δ13C values near −20‰ PDB suggest hydrocarbon production by high-temperature maturation of sedimentary organic matter and mixing (∼1:1) of the thermogenic CH4 with abiogenic CH4. Long-chained hydrocarbons occur in dredged samples close to the active vents. Their n-alkane distribution has a high to moderate odd–even predominance and an extensive hopane series, indicative of higher land-plant waxes and prokaryotic membranes in the source. Substantial amounts of unsubstituted polynuclear aromatic hydrocarbons (PAH) mark the transition from aliphatic- to aromatic-dominated bitumens, consistent with extensive source maturation resulting from thermal stress. The bitumens are interpreted as pyrolysates derived from buried near-coastal vegetation and terrestrial detritus under various thermal regimes, mixed with immature seafloor organic matter.